모바일 IAB를 향한 UxNB 망구축 방안에 관한 연구 - 김기원(Keewon Kim); 김종현(Jonghyun Kim); 박경민(Kyungmin Park); 박태근(Tae-Keun Park) (한국컴퓨터정보학회논문지, 2023)
본 논문은 모바일 IAB를 향한 UxNB 네트워크 배포 및 운영 방안을 제안한다. SDN(Software Defined Network) 기반으로 UxNB 네트워크를 운영하여, 이동 통신 서비스를 원하는 지역에 UxNB를 배포한다. 서비스 지역에 UxNB를 배포한 후, IAB를 설정하여 이동 통신 서비스를 수행할 수 있다. 이를 위해본 논문에서는 먼저 UAV 컨트롤러(UAV controller)와 SDN 컨트롤러(SDN controller)로 구성되는 UxNB 네트워크 컨트롤러(UxNB NC; UxNB network controller)를 제안하고 필요한 기능들을 기술한다. 다음으로 UxNB 네트워크를 배포하고 운영할 수 있는 시나리오를 단계별로 상세하게 제시한다. 또한 UxNB 네트워크 컨트롤러의 위치, UxNB에 대한 UAV 컨트롤러 제어 명령 전달 방법, UxNB 네트워크를 위한IAB 적용 방법, UxNB 네트워크의 최적화, UxNB 네트워크의 RLF(radio link failure) 복구 및 UxNB 네트워크의 보안(security)에 대한 향후 연구를 논한다. 제안한 UxNB NC 아키텍처와 UxNB 네트워크 배포및 운영 방안을 이용하여 모바일 IAB에 UxNB 네트워크를 원활하게 통합할 수 있을 것으로 기대한다. In this paper, we propose a deployment and operation scheme of UxNB network toward mobile IAB. By operating a UxNB network based on SDN(Software Defined Network), UxNBs are deployed in areas where mobile communication services are desired. After deploying UxNB in the service area, IAB can be set up to perform mobile communication services. For this purpose, this paper first proposes a UxNB Network Controller consisting of a UAV Controller and an SDN Controller, and proposes the necessary functions. Next, we present a scenario in which a UxNB network can be deployed and operated in detail step by step. We also discuss the location of the UxNB network controller, how to deliver control commands from the UAV controller to the UxNB, how to apply IAB for UxNB networks, optimization of UxNB networks, RLF(radio link failure) recovery in UxNB networks, and future research on security in UxNB networks. It is expected that the proposed UxNB Network Controller architecture and UxNB network deployment and operation will enable seamless integration of UxNB networks into Mobile IAB. KCI Citation Count: 0